Exploring human figure drawings as an assessment tool for departing OFW domestic helpers and caregivers - Dans-Lopez, Gilda (Philippine Journal of Counseling Psychology, 2010)
This study intended to find specific indicators that would objectify assessment of drawings of Overseas Filipino Workers (OFW's). Drawings of 273 females departing for the Middle East as domestic helpers or caregivers were analyzed. Thirty-two specific indicators were found to be significantly related to global artistic quality and bizarreness. These included details about size, placement, proportion, transparencies, gender/age representation, and omission/overemphasis of body features. Results revealed that global indicators of overall quality, bizarreness, and specific indicators were discriminated by age and educational attainment of the participants. Those with only high school education had poorer drawings compared to those with some college or a college degree. Those aged 26 to 32 were likewise found to have poorer drawings compared to the youngest and eldest participants. Findings generally reveal the potential of the use of human figure drawings as a screening tool not only for OFW's but for different groups of Filipino adults as well. Implications of the findings and directions for future studies are discussed.